Virial Moments of Large-Scale Neutrino Structures - Dhungel, PR; Sharma, SK; Khanal, U (Scientific World, 2010)
In the course of studying the role of massive neutrinos and other particles in the large scale structures formation in the universe, Virial moments of the neutrino structures have been calculated. The Jeans masses calculated this way have been compared with the ones calculated earlier in our previous paper. Key words: Large-scale structures; Virial equation; Neutrino; Jeans mass. DOI: 10.3126/sw.v8i8.3837 Scientific World Vol.8(8) 2010 pp.1-3